Seminar and Workshop on Making Centing Sukaliya (Prevent Stunting Together with Soybean Milk and Aloe Vera) and Its Utilization for Preventing Stunting in Toddlers in Demakan Village, Mojolaban Subdistrict, Sukoharjo Regency (STIKes Mitra Keluarga, 2024)
Stunting is a condition of malnutrition that is related to insufficient nutrition, so it is a chronic nutritional problem. This chronic condition requires efforts to prevent stunting, many programs and products to minimize the increase in the incidence of stunting in Indonesia. Aloe vera (Aloe vera) and soybeans are plants that have the potential to be used as food ingredients to prevent stunting because they contain nutrients, namely protein, fat, carbohydrates, calcium, phosphorus, iron and vitamin B1. The intended targets were mothers of toddlers at mangosteen posyandu 1 Demakan Village, Mojolaban Village, Sukoharjo Regency. Based on the results of the product liking assessment, it was found that the audience liked the product given, namely aloe vera soy milk. Based on the results of the pretest and posttest, it can be concluded that the audience's insight increased from before the counseling was carried out and after the counseling was carried out.